Effect of different particle-sized lotus leaf powder dried by different conditions on shelf-life of green wheat leaf beverage - Guo, Panpan; Qiu, Zhuangzhuang (Frontiers in Sustainable Food Systems, 2025)
IntroductionThis study aimed to investigate the effect of antioxidant activities of lotus leaf powder (LLP) with different particle sizes on the shelf-life of green wheat leaf beverage (GWLB), so as to provide a theoretical basis for improving the quality and extending the shelf-life of GWLB This study aimed to investigate the effect of antioxidant activities of lotus leaf powder (LLP) with different particle sizes on the shelf-life of green wheat leaf beverage (GWLB), so as to provide a theoretical basis for improving the quality and extending the shelf-life of GWLB.MethodsOven-dried LLP was used as the experimental material, and different concentrations (0%, 0.25%, 0.5%, and 1%) of LLP were added to GWLB respectively. The total phenolic compounds (TPCs), 1,1-diphenyl-2-picrylhydrazyl (DPPH) radical scavenging activity, ferrous iron chelating activity (FICA), and ferric reducing power ability (FRPA) of LLP dried at 60 °C were determined. Meanwhile, the pH value, total bacterial count, color indicators (lightness, yellowness, redness), soluble solids content, suspension stability, and antioxidant activity of GWLB with different LLP additions were monitored during storage.ResultsAmong all LLP treatments, the LLP dried at 60 °C had the highest levels of TPCs (7.57 g/100 g), DPPH radical scavenging activity (18.76–44.69%), FICA (57.26–79.03%), and FRPA (0.76–1.33 O.D.). After adding LLP to GWLB, the antioxidant capacity of GWLB was enhanced, the pH value was lower, and the number of microorganisms was reduced. Specifically, the pH value of GWLB with 1% T1LLPS (a type of LLP) added was 7.26, while that of GWLB without T1LLPS added was 7.69. On the third day of storage, the total bacterial count of GWLB without T1LLPS added was 2.11 Log CFU/mL, whereas that of GWLB with 1% T1LLPS added was less than 2.00 Log CFU/mL. In addition, the lightness, yellowness values, and soluble solids contents of GWLB increased after LLP addition, while the redness values and suspension stability decreased. During storage, the GWLB with 1% LLP added showed the highest antioxidant activity among all treatment groups.DiscussionThe addition of LLP can effectively improve the antioxidant capacity of GWLB, inhibit the growth of microorganisms, and adjust the physical and chemical properties of GWLB (such as pH value, color, and soluble solids content). Among all concentrations, 1% LLP addition exhibited the best effect, which not only had the highest antioxidant activity during storage but also significantly extended the shelf-life of GWLB. This indicates that LLP has good application potential in the processing and preservation of GWLB.